(3GdRjL GdehLRs - (3GdeanqVd Hf YeQ Hf GdeaVd GdCHgQj GdSeQbfOj, CKjQ GdOjf,J (B663 (3g` s
(3ChdgG (B:s
(3Gdbhd ai MSGH GdMQcGJ GdadcjI hgh GdehSe HGdRjL GYde Gf GdJhGQjN GdeSJYedI ai ReGffG GQHYI Qhei hYQHi haGQS hedci s
(3BNQgG (B:s
(3aeG Hbi agh eWGdY ai eWGdY NW GdESJhGA djNQL gPg GdHjhJ hGddg CYde HGdUhGH s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGdKIs
(3GfXQg eY GdeNWhW Qbe (B169 (3ef faS GdHYKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B969s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eTgO (B- (3cdjI GdEdgjGJ (B(3/51) s
Keywords: (3Gdadcs